2020
DOI: 10.1186/s40795-020-00399-8
|View full text |Cite
|
Sign up to set email alerts
|

Community-based nutrition-sensitive approach to address short-term hunger and undernutrition among primary school children in rural areas in a developing country setting: lessons from North and North-Eastern Uganda

Abstract: Background Undernutrition in childhood is an important factor that greatly impedes the achievement of full human potential at adulthood. Despite increased enrolment of pupils in primary schools in developing countries, short-term hunger and undernutrition continue to impact negatively on school attendance, retention and education outcomes in economically disadvantaged rural areas. This study examined the feasibility of a community-based participatory action research approach building capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Relatedly, previous studies suggested that more youthful mothers or child caregivers may participate in broader economic activities such as small trade which can widen their access to more and better diverse foods [ 38 ]. On the otherhand, as previous scholars such as [ [39] , [40] , [41] , [42] ] emphasized the need for nutritional education, we observe in this study that integration of nutritional training in antenatal care programs greatly influences the feeding practices, dietary diversity and has a strong positive association with household food security. It is therefore apparent that nutritional education should be an integral part of training for mothers and caregivers of infants and young children.…”
Section: Discussionmentioning
confidence: 49%
“…Relatedly, previous studies suggested that more youthful mothers or child caregivers may participate in broader economic activities such as small trade which can widen their access to more and better diverse foods [ 38 ]. On the otherhand, as previous scholars such as [ [39] , [40] , [41] , [42] ] emphasized the need for nutritional education, we observe in this study that integration of nutritional training in antenatal care programs greatly influences the feeding practices, dietary diversity and has a strong positive association with household food security. It is therefore apparent that nutritional education should be an integral part of training for mothers and caregivers of infants and young children.…”
Section: Discussionmentioning
confidence: 49%
“…From a cultural standpoint, school menus based on local food preparations are associated with greater acceptance by the school community, as well as contributing to the preservation of food habits, biodiversity conservation, and sustainability [33]. In addition, the underutilization of locally available food resources and lack of knowledge about their food potential reduce opportunities for the inclusion of strategic foods in school meals, especially in economically disadvantaged areas [39].…”
Section: Consumptionmentioning
confidence: 99%
“…There is a growing awareness of the power of institutional food services to promote sustainable food production and consumption through healthy food procurement strategies [1,2]. The direct purchase policy of family-farming food in the School Feeding Program can contribute to developing more sustainable agrifood systems by reducing poverty and social inequality [3,4], improving school meal quality [5][6][7], encouraging the incorporation of regional foods in school menus [8], diversifying family farm income sources [9] and increasing food security and nutrition [10][11][12].…”
Section: Introductionmentioning
confidence: 99%